Harmonization of Law on the Future Challenges of Notaries in Indonesia in Facing the Cyber Notary Era - Agustan, Fajar; Syahputra, Robert Dicky; Hafizh, Sulthan; Navisa, Fitria Dewi (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
This article discusses the harmonization of law in facing the future challenges of notaries in Indonesia in the Cyber Notary era. With the development of technology, traditional notary practices have undergone a significant transformation towards digitalization, creating a need to review the existing legal framework. This article focuses on two main problem formulations. First, the analysis of the suitability of laws and regulations with the needs of Cyber Notary practices in Indonesia. This evaluation includes whether existing regulations, such as the Notary Law, the Regulation of the Minister of Law and Human Rights, and the Law on Information and Electronic Transactions are sufficient to support electronic notaries and how legal harmonization can improve the certainty and effectiveness of notary services. Second, the interpretation and adaptation of existing legal principles to address legal and ethical challenges in the Cyber Notary era. This article examines aspects of document validity, personal data protection, and notary responsibilities in the context of digitalization. The main objective is to identify emerging legal challenges and provide recommendations for legal harmonization that can ensure integrity and trust in the notary profession in the digital era.